Pengaruh Konten Instagram Dalam Kampanye Penggalangan Dana Di LAZ Dompet Amanah Umat (International Forum of Researchers and Lecturers, 2024)
Analysis of the influence of visual content in the fundraising campaign for zakat by Lembaga Amil Zakat Dompet Amanah Umat (LAZDAU) on the Instagram platform during August to October 2023. Employing a qualitative descriptive method with the approach of decision-making theory and customer engagement, this research highlights how consumers interact, respond, and engage with the visual design of LAZDAU's content. The findings reveal that content with clear and consistent visual designs, receiving positive responses from the audience, directly impacts the participation and success of the fundraising campaign, reflected in the significant financial reception by LAZDAU. This journal underscores the crucial role of appropriate visual design in enhancing community participation and responsiveness to humanitarian efforts within zakat institutions.